1975
DOI: 10.1161/01.cir.52.5.799
|View full text |Cite
|
Sign up to set email alerts
|

Precordial ST-segment mapping 1. Clinical studies in the coronary care unit.

Abstract: SUMMARYPrecordial ST-segment mapping was applied serially in the coronary care unit for the study of 46 patients with myocardial infarction (MI), using a 49-lead system. Data from the maps were compared with clinical status of patients, conventional ECGs obtained simultaneously, and serum enzyme levels. Stability of the maps over a one hour period was noted in the early phase of admission. However, a The present study reports on the results of serial precordial mapping applied in patients treated in the CCU … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
3

Year Published

1976
1976
2000
2000

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(18 citation statements)
references
References 37 publications
2
13
0
3
Order By: Relevance
“…In contrast, epicardial ST segment voltages were highest just inside the cyanotic border and decreased progressively toward the center of the ischemic region. As seen in figure 6, these increases in total ST segment voltage were due to a combination of true ST elevation and TQ segment depression. The relative contribution of TQ segment depression, however, was greater in recordings made inside the ischemic region der of the cyanotic region was determined in six dogs by the radioactive microsphere technique.…”
Section: Resultsmentioning
confidence: 86%
“…In contrast, epicardial ST segment voltages were highest just inside the cyanotic border and decreased progressively toward the center of the ischemic region. As seen in figure 6, these increases in total ST segment voltage were due to a combination of true ST elevation and TQ segment depression. The relative contribution of TQ segment depression, however, was greater in recordings made inside the ischemic region der of the cyanotic region was determined in six dogs by the radioactive microsphere technique.…”
Section: Resultsmentioning
confidence: 86%
“…Reese and co-authors found wide variability in 2ST after AMI, and noted that re-elevations were not always associated with infarct extension. '3 Madias et al,6 who studied 37 patients with AMI, found evidence for infarct extension in 18. One patient with subendocardial ischemia had a progressive increase in ST depression, evolved an anterior transmural MI and died in cardiogenic shock.…”
Section: Discussionmentioning
confidence: 99%
“…Precordial ST-segment mapping provides a useful noninvasive approach for the assessment of acute directional changes in ischemic injury that appears to be a reliable clinical indicator of particular therapeutic interventions.14 29,[32][33][34][35][36][37][38][39] More rapid reductions of ST-segment elevations were observed in patients with the inhalation of oxygen39 and the use of drugs such as hyaluronidase,33 nitroglycerin (with and without phenylephrine37, 38), as well as with intra-aortic balloon counterpulsation,29 than in untreated patients. The same interventions have been shown to reduce infarct size in experimental animals, and these changes in the ST segment appear to correlate well with the salvage of myocardium.…”
Section: An Official Journal Oftle American Heart Association Editorimentioning
confidence: 99%